Micropropagation of Medicinal Plants: Techniques for Thyme (Thymus Vulgaris) and Rosemary (Rosmarinus Officinalis) - Shokirova Gavkharkhan Nazigulomovna; Rasulova Sarvinoz daughter of Khairulla (Scientific Trends, 2025)
Micropropagation is a vital biotechnological tool for the rapid and efficient multiplication of medicinal plants, ensuring the conservation of genetic traits and the production of high-quality plant material. This review focuses on the micropropagation protocols developed for Thymus vulgaris and Rosmarinus officinalis, two aromatic and medicinal species of significant economic importance. The paper discusses the selection of explants, the composition of culture media, the role of plant growth regulators, and the acclimatization processes, providing a comprehensive overview of the methodologies employed in the in vitro propagation of these plants.
Keywords: Micropropagation, Thymus vulgaris, Rosmarinus officinalis, tissue culture, plant growth regulators, acclimatization, genetic stability, essential oils.